Completing an Economics PhD in Five Years - Stock, Wendy A; Finegan, T. Aldrich; Siegfried, John J (American Economic Review, 2009)
Although the median time-to-degree for economics PhDs was near 5.5 years in 2002, and appears to be rising (Stock and Siegfried 2006), some students can and do earn the degree in under five years. Of 586 individuals who began PhD study in economics in 2002, 27 percent had a diploma they could display on their office wall by fall 2007. Many economics PhD programs advertise that it normally takes five years to earn the degree. Some programs encourage completion by limiting financial aid to five years. Students who take more than five years incur high opportunity costs of remaining in school, as their Completing an eConomiCs pHD in Five Years: let tHe Data (literallY) speak For tHemselves †